The Urgency Of Digitalizing Hospital Administration To Improve Patient Care - Inayatul Aini (CV. Inara, 2024)
Health information technology is used for various purposes in health care facilities. Benefits for health care providers include improving the quality of data and information, improve service quality, reduce data redundancies, reducing clinical errors, and accelerating access to patient data. The method of this study is a scoping literature review using international and national publications through various databases in terms of research articles, report, and working papers using keywords hospital and digital. The type of research used in this study is descriptive research with a qualitative approach.. SIMRS implementation can improve hospital efficiency in terms of process or service flow. This encourages reduced hospital operating costs, improve hospital performance, improve the ability of human resources in the hospital, and develop hospital organizations towards the ability of human resources in the hospital, as well as developing the hospital organization in a better direction.